Pengaruh Pola Makan Tinggi Kalori terhadap Peningkatan Kadar Gula Darah pada Penderita Diabetes Mellitus Tipe 2 - Ahmad Baequny; Afiyah Sri Harnany; Elsye Rumimper (Jurnal Riset Kesehatan, 2015)
The research objective is to describe about high-calorie diet to increase blood sugar levels in people with Type 2 Diabetes Mellitus. Population and sample in this study are patients with type 2 Diabetes at the health center Bendan Pekalongan. This is a descriptive analytic study with cross-sectional design and analyzed using chi square test. The results show that there is an effect of high-calorie diet in the increase of blood sugar levels in people with type 2 diabetes mellitus in PHC Bendan Pekalongan (p value 0.018). To improve the adherence of patients in the treatment program and manage blood sugar levels, it is advisable for patients to comply with dietary adjustments that have been recommended by the officers in the scope of type, quantity and schedule of the diet. The health workers are also expected to continue to provide motivation, information and health education for patients and their families to improve their knowledge and awareness so that the patient's blood sugar levels can be controlled properly.